Awareness and knowledge about glaucoma among patients attending the health centers related to the primary healthcare corporation in Qatar - Alauglha, Rime H.; Mechrgui, Monia S. (International Journal of Research in Medical Sciences, 2025)
Background: Public awareness of eye diseases can influence the use of eye care services and preventive behaviors. Raising awareness about glaucoma is essential for early detection and blindness prevention. However, the level of awareness at the community level in Qatar remains unclear, making targeted interventions challenging. Objective was to assess the awareness and knowledge of glaucoma among adult patients attending ophthalmology clinics at primary health care corporation (PHCC) centers in Qatar. Methods: A cross-sectional study was conducted among 300 participants (175 males and 125 females) using a structured questionnaire. The survey collected demographic information and assessed awareness of glaucoma. Statistical analyses included descriptive statistics, Chi-square, ANOVA, and Pearson correlation. Results: Overall, less than half of participants (131/300) aware of glaucoma. The most common source of information was knowing someone affected by disease (15.7%). Educational level had a significant impact: those with higher education were more aware (48.1%) than those with lower education. Females (51.6%) showed higher awareness than males (38%). Age group 50–60 had the highest awareness (50%), and Arabic speakers were the most informed (52.3%). Conclusions: Awareness and knowledge about glaucoma among PHCC patients in Qatar were generally low. Public health initiatives should prioritize educational campaigns focusing on risk factors, complications, and the importance of regular eye examinations for early detection and management.